2010
DOI: 10.1111/j.1365-2362.2009.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Pim‐3 protects against hepatic failure in D‐galactosamine (D‐GalN)‐sensitized rats

Abstract: Pim-3 gene could protect rats from FHF by inhibiting liver apoptosis and improving inflammatory response of liver tissues, which could be associated with inhibiting expression of inflammatory mediators and promoting expression of anti-apoptosis protein Bcl-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…In other words, the mechanism of the inhibitory effects, by which TQ protects against lipid peroxidation, may involve radical scavenging capability. Hepatotoxicity not only initiates lipid peroxidation but also reduces tissue GSH-px, GST, CAT, and SOD activities, and this depletion may result from oxidative modification of these proteins and our data are in line with other previous studies [3236]. …”
Section: Discussionsupporting
confidence: 93%
“…In other words, the mechanism of the inhibitory effects, by which TQ protects against lipid peroxidation, may involve radical scavenging capability. Hepatotoxicity not only initiates lipid peroxidation but also reduces tissue GSH-px, GST, CAT, and SOD activities, and this depletion may result from oxidative modification of these proteins and our data are in line with other previous studies [3236]. …”
Section: Discussionsupporting
confidence: 93%
“…At 30 min after the injection, mice (NS, urantide) were challenged by an intraperitoneal injection with a total volume of 200 µl of NS (sham) or with 800 mg⋅kg −1 GalN and 50 µg⋅kg −1 LPS dissolved in 200 µl of NS as previously described [5] (LPS/GalN, urantide+LPS/GalN). Animal survival rates were calculated at 1, 2, 4, 6, 8, 12, 24 and 48 h after LPS/GalN injection, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As an animal model of ALF, lipopolysaccharide (LPS)/D-galactosamine (GalN)-challenged mice showed massive apoptosis in liver [4], [5]. Through crosstalking with innate immune system, the drugs can initiate the early immune injury of liver by stimulating production of proinflammatory cytokines [6].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that the SHANK3 gene product may play a role in autoimmunological response. The deleted region also includes the oncogene PIM3 which has previously been associated with liver disease in rats [Liu et al, 2010]. PIM3 encodes a serine/threonine protein kinase that is reported to be aberrantly expressed in human and mouse hepatitis but not normal liver.…”
mentioning
confidence: 99%